Adaptation Strategies Affecting the Survival During the COVID-19 of Entrepreneurs in Ban Tawai Handicraft Tourism Community, Hang Dong District, Chiang Mai Province - Sitthikun, Suthira; Leelapattana, Winitra; Thongma, Weerapon (Research and Development Journal, Loei Rajabhat University, 2025)
This study aimed to: 1) Assess the economic impact of the COVID-19 crisis; 2) Examine the strategic factors influencing adaptation and survival; and 3) Analyze the adaptation strategies affecting the survival of entrepreneurs in the Ban Tawai Handicraft Tourism Community, Hang Dong District, Chiang Mai Province. The sample consisted of 220 entrepreneurs selected through a convenient sampling method. Data was collected using a questionnaire, and the analysis was conducted using basic descriptive statistics, including mean, standard deviation, and multiple regression analysis. The findings are as follows: 1) Entrepreneurs experienced significant economic impacts, particularly in terms of a sharp decline in household income, financial instability, worsening living conditions, and the inability to carry out regular business activities; 2) The strategic adaptation process involved the establishment of business networks, development of unique products, digital marketing strategies, tourism experience design, and the integration of technology to enhance operational efficiency. These adaptations were implemented at a high level; 3) Factors contributing to survival included increased customer confidence in the shop's image, products, and services; a growing base of repeat customers; increased sales and profits; business expansion of the opening of new branches; and a higher influx of new customers. These factors collectively played a significant role in supporting the survival of entrepreneurs; 4) The use of technology and effective cost management were identified as critical strategic factors that significantly contributed to the survival of entrepreneurs in the Ban Tawai handicraft tourism community during the COVID-19 crisis.